Organoamido zirconium(iv) and titanium(iv) complexes and their catalysis towards ethylene polymerization. Issue 127 (14th December 2015) - Zhou, Meisu; Yang, Qiaokun; Tong, Hongbo; Yan, Lei; Wang, Xiaoyang
Abstract : Novel organoamido zirconium(iv ) and titanium(iv ) complexes, their structural features and catalytic activity in the polymerization of ethylene are reported. Abstract : The reaction of PhN(Li)SiMe3 with 2 equiv. of dimethylcyanamide with further addition of 2 equiv. of CpTiCl3 led via Me3 SiCl elimination to dinuclear titanium(iv ) compound1 . The reaction of DippN(Li)SiMe3 with 1 equiv. of dimethylcyanamide with further addition of 1 equiv. of CpTiCl3 afforded centrosymmetric dimeric titanium(iv ) compound2 and mononuclear3 with the elimination of Me3 SiCl. The zirconium(iv ) compound4 was obtained by the addition reaction of PhN(Li)SiMe3 with 2 equiv. of dimethylcyanamide and metathesis reaction with ZrCl4 . X-ray diffraction studies of1–4 establish the dinuclear titanium(iv ) structure in1, half-titanocene of2 and3, and a propeller-like complex fragment of4 . Complexes2 and4 show moderate or high activities in the polymerization of ethylene upon activation with methylaluminoxane (MAO).